The Influence of Liquidity, Solvency and Profitability on Company Stock Prices Food and Beverage Subsector - Fahrizah, Ismah; Sofyaun, Ashari; Matyani, Matyani (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to test the influence of liquidity as measured by the Current Ratio and Solvency as measured by Debt to Equity Ratio and Profitability with Return On Equity proxy on Stock Price. The data used is secondary data from the Annual Report. The sample used in this study was 15 companies in the Food and Beverage subsector. listed on the Indonesia Stock Exchange that meets the requirements for use in research with a period from 20 20 to 2023 ( 4 years), so that the data observed is 60. This study uses a quantitative method with SPSS analysis tools. The findings of this study indicate that liquidity has a positive effect on stock prices. Sol vability and profitability partially do not affect stock prices